2012
DOI: 10.1093/carcin/bgs166
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-93 inhibits tumor growth and early relapse of human colorectal cancer by affecting genes involved in the cell cycle

Abstract: This study showed that microRNA-93 can inhibit tumorigenesis and reduce the recurrence of CRC; these findings may have potential clinical applications for predicting the recurrence of CRC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
67
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(73 citation statements)
references
References 42 publications
4
67
0
Order By: Relevance
“…[27][28][29] Their results are complementary to ours and suggest that dysregulated miRNAs in tumours could predict recurrence of CRC.…”
Section: Discussionsupporting
confidence: 73%
“…[27][28][29] Their results are complementary to ours and suggest that dysregulated miRNAs in tumours could predict recurrence of CRC.…”
Section: Discussionsupporting
confidence: 73%
“…*P < 0.05 vs. sham group; # P < 0.05 vs. I/R + miR control group Until now, studies of miR-93 have been focused mainly on its involvement in many types of human cancers, such as glioblastoma, gastric cancer, breast carcinoma, and others. miR-93 is overexpressed in a number of types of human cancers and functions as an oncogene by targeting important cancer-related genes [25][26][27][28][29], whereas, in some types of cancers miR-93 was down-regulated and repressed proliferation paradoxically [30,31]. However, the present study is the first to investigate its role in ischemia-induced cerebral injury.…”
Section: Mir-93 Antagomir Induced Ho-1 Expression Through Nrf2mentioning
confidence: 67%
“…Several previous studies have indicated that miR-93, miR-195, and members of the let-7 family of miRs are downregulated in lung cancer, CRC, and melanoma tissues as compared with normal tissue, suggesting that these miRs are tumor suppressors [29][30][31][32][33][34][35][36][37]. miR-93 can suppress the proliferation of human colon cancer cells and colon cancer stem cells, with worse OS being associated with low miR-93 expression in CRC patients [37,38].…”
Section: Discussionmentioning
confidence: 99%